Farmakoterapie po srdecním infarktu - Spinarová, L; Spinar, J; Vítovec, J (Vnitrni lekarstvi, 2011)
Early reperfusion is the treatment of choice for acute coronary syndrome. In the Czech Republic, reperfusion therapy is well accessible thanks to the network of 22 catheterization centres. Every year, 28,000 patients are treated using this technique. Successful reperfusion should be followed by life style changes--smoking cessation, maintenance of appropriate body weight etc. These steps than has to be accompanied by effective pharmacotherapy to prevent remodelling of the left ventricle, re-stenosis of the coronary artery, re-thrombosis and arrhythmias. Four drug groups provide the desired effects--renin-angiotensin-aldosterone system blockers, beta-blockers, antiplatelet agents and statins.
Keywords: statiny; Myocardial Infarction; inhibitory agregace trombocytů; Adrenergic beta-Antagonists; inhibitory ACE; lidé; Hydroxymethylglutaryl-CoA Reductase Inhibitors; beta blokátory; Platelet Aggregation Inhibitors; Angiotensin-Converting Enzyme Inhibitors; infarkt myokardu; Humans